A Robust Causal Order Protocol - Lima, George Marconi de A.; Macêdo, Raimundo J. de A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1999: Anais do XI Symposium on Computer Architecture and High Performance Computing, 1999)
This paper presents a robust causal order protocol implemented for the BCG platform (Reliable Group Communication Base) developed at LaSiD/UFBA (Distributed System Laboratory at UFBA). It was designed using a symmetric message recovery approach in which any process of the group can detect and retransmit missing messages providing a reliable message recovery mechanism. Its algorithm, based on certain properties and structures of the BCG, makes the proposed protocol more flexible than similar protocols published to date. Data collected from experiments are also reported.